Enhancing the student learning experience: Co‐teaching biochemistry and clinical sciences within the dental curriculum. Issue 2 (7th December 2022) - Zhao, Rusin; Wang, Tao; Yang, Ruijia; Adam, Lee A.; Zaharic, Tony; Loch, Carolina; Tompkins, Geoffrey R.; Cooper, Paul R.
Abstract: Basic knowledge of biochemistry underpins oral and dental care. Undergraduate dental students do not always engage well with basic science teaching due to not appreciating its clinical relevance. Co‐teaching provides one approach to overcome students' disengagement and involves two lecturers, with complementary expertise, presenting the curriculum together. This study investigated student experiences and engagement using co‐teaching to integrate biochemistry with clinical sciences in the students' second‐year dental curriculum. Two successive second year dental student cohorts were co‐taught. Content was delivered by a biochemist and an oral biologist, either online (during the 2020 COVID lockdown) or in‐person (2021). Each cohort was surveyed at the end of the teaching module using an online questionnaire containing both interval scale and free‐text questions. Responses were received from 39 (42%) and 64 (85%) of students in 2020 and 2021, respectively. Students from both cohorts preferred the co‐teaching approach with a mean of 8.74 on a 10‐point interval scale. In 2020 and 2021, 77% and 76% of participants, respectively, preferred a combined biochemistry and clinical dentistry delivery, either in‐person (37%), via Zoom (19%) or via video recording (14%). Thematic analysis of responses revealed students experienced enhanced engagement when co‐taught and they attributed this to integration of the curriculum making the content more relevant and stimulating. Students preferred co‐teaching to individual subjects being taught by a single teacher. Co‐teaching established the relevance of theoretical biochemistry to clinical dental sciences and enhanced the students' learning experience.